A voltage control scheme in a distribution feeder with wind energy sources - Petinrin, J. O. (2015)
The allure of integrating wind power, as a clean renewable energy source, into distribution grids is usually blurred with its undesirable impacts. These include reverse power flow, voltage rise, and disruption of the normal operation of voltage/VAr (VVAr) control devices. This paper describes a voltage control scheme that coordinates the VVAr control devices along with energy storage to mitigate integration issues associated with wind generation. The proposed voltage control scheme is formulated as a nonlinear programming problem to minimize voltage deviations and power losses. A hybrid Particle Swarm Optimization-Gravitational Search Algorithm (PSOGSA) is used to solve the resulting optimization problem. The solution provides the hourly operation schedule of the VVAr control devices as well as the size and location of the energy storage. Test results confirm the effectiveness the energy storage together with the coordination of the VVAr devices to maintain the system voltage within the prescribed limits.